Safety of elective paediatric surgery during the coronavirus disease 2019 pandemic. (November 2021) - Kavanagh, F.G.; James, D.L.; Brinkman, D.; Cornyn, S.; Murphy, C.; O'Neill, S.; O'Shea, R.; Affendi, A.; Lang, B.; O'Connor, A.; Keogh, I.; Lang, E.; et al.
Abstract: Introduction: Corona-virus Disease 2019 (COVID-19) has had a huge impact on the delivery of healthcare worldwide, particularly elective surgery. There is a lack of data regarding risk of postoperative COVID-19 infection in children undergoing elective surgery, and regarding the utility of pre-operative COVID-19 testing, and preoperative "cocooning" or restriction of movements. The purpose of this present study was to examine the safety of elective paediatric Otolaryngology surgery during the COVID-19 pandemic with respect to incidence of postoperative symptomatic COVID-19 infection or major respiratory complications. Materials and methods: Prospective cohort study of paediatric patients undergoing elective Otolaryngology surgery between September and December 2020. Primary outcome measure was incidence of symptomatic COVID-19 or major respiratory complications within the 14 days after surgery. Parents of prospectively enrolled patients were contacted 14 days after surgery and enquiry made regarding development of postoperative symptoms, COVID-19 testing, or diagnosis of COVID-19. Results: 302 patients were recruited. 125 (41.4%) underwent preoperative COVID-19 RT-PCR testing. 66 (21.8%) restricted movements prior to surgery. The peak 14-day COVID-19 incidence during the study was 302.9 cases per 100, 000 population. No COVID-19 infections or major respiratory complications were reported in the 14 day follow-up period. Conclusion: The results of our study support the safety of elective paediatric Otolaryngology surgery during the pandemic, in the setting of community incidence not exceeding that observed during the study period. Highlights: Corona-virus Disease 2019 had had a major impact on healthcare delivery globally. It is safe to proceed with elective paediatric surgery during the current pandemic when community transmission levels are low. Further work is required to elucidate the exact role of 'cocooning'/self-isolating in the role of disease prevention.